2006
DOI: 10.1111/j.1469-8137.2006.01847.x
|View full text |Cite|
|
Sign up to set email alerts
|

Fine‐root turnover patterns and their relationship to root diameter and soil depth in a 14C‐labeled hardwood forest

Abstract: Summary• Characterization of turnover times of fine roots is essential to understanding patterns of carbon allocation in plants and describing forest C cycling. We used the rate of decline in the ratio of 14 C to 12 C in a mature hardwood forest, enriched by an inadvertent 14 C pulse, to investigate fine-root turnover and its relationship with fine-root diameter and soil depth.• Biomass and ∆ 14 C values were determined for fine roots collected during three consecutive winters from four sites, by depth, diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(169 citation statements)
references
References 53 publications
9
158
0
2
Order By: Relevance
“…This could be linked to an overestimation of C input from tree fine root mortality. Indeed, a constant root turnover was considered along the soil profile, but several authors reported a decrease in the root turnover with increasing soil depth (Germon et al, 2016;Hendrick and Pregitzer, 1996;Joslin et al, 2006). However, the sensitivity analysis showed that the model was not sensitive to this parameter (Fig.…”
Section: Representation Of Soc Spatial Heterogeneity In Agroforestry mentioning
confidence: 99%
“…This could be linked to an overestimation of C input from tree fine root mortality. Indeed, a constant root turnover was considered along the soil profile, but several authors reported a decrease in the root turnover with increasing soil depth (Germon et al, 2016;Hendrick and Pregitzer, 1996;Joslin et al, 2006). However, the sensitivity analysis showed that the model was not sensitive to this parameter (Fig.…”
Section: Representation Of Soc Spatial Heterogeneity In Agroforestry mentioning
confidence: 99%
“…Thus, there is potential for a species' litter decomposition to be controlled largely by location in the soil profile. For example, there are slower turnover and decomposition rates of root litter at deeper depths in the soil profile (Gill and Burke, 2002;Joslin et al, 2006;McCormack et al, 2010). Recently, Schweigert et al (2015) traced the fate of 13 C-labeled Laccaria bicolor biomass amendments in an in vitro soil bioreactor experiment.…”
Section: Physical and Spatial Protectionmentioning
confidence: 99%
“…CLM4 calculates root distributions for plant water uptake based on a double-exponential function (Zeng, 2001); in principle, however, the vertical profiles of root C and N inputs to soil need not be identical to those of plant water uptake from soil due to differing root lifetimes (Joslin et al, 2006;Riley et al, 2009) for different types of roots. Thus, one hypothesis is that C inputs are proportional to the root profiles used in the water uptake calculations.…”
Section: Vertical Discretization Of Carbon Inputsmentioning
confidence: 99%
“…Because of the dependence of soil heterotrophic respiration and the resulting CO 2 release on environmental conditions, climate change may lead to potentially large positive feedbacks with the atmosphere (Jenkinson et al, 1991). The current generation of coupled carbon-climate models have high uncertainty in the magnitude of carbon cycle feedbacks (Friedlingstein et al, 2006;Arora et al, 2013), and a dominant source of this uncertainty is associated with SOM sensitivity to environmental change (Jones et al, 2003). In addition to a direct role in the global C cycle through SOM decomposition and CO 2 production, SOM plays a crucial role in soil nutrient feedbacks -in particular, C-N couplings -because decomposing SOM provides mineralized N for vegetation growth.…”
Section: Introductionmentioning
confidence: 99%